Estimation of Ground Water Recharge Using Soil Moisture Balance Approach - Kumar, C.P. (Journal of Soil and Water Conservation, 2022)
The amount of water that may be extracted from an aquifer without causing depletion is primarily dependent upon the ground water recharge. A quantitative evaluation of spatial and temporal distribution of ground water recharge is a pre-requisite for operating ground water resources system in an optimal manner. This paper presents a methodology with step-by-step procedure to determine the ground water recharge by soil moisture balance in the unsaturated zone.